2011
DOI: 10.4149/neo_2011_03_245
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival and cancer recurrence using F-18 FDG PET/CT in patients with surgically resected early stage (Stage I and II) non-small cell lung cancer

Abstract: The aim of the current study was to investigate the prognostic value of SUV max in patients with completely resected early stage (stage I & II) NSCLC.A retrospective review identified 76 patients with surgically resected early (stage I and II) NSCLC who received F-18 FDG PET/CT at diagnosis of cancer. Survival analysis was conducted using Kaplan-Meier analysis, and survival curves stratified by age, sex, mediastinal lymph node involvement, SUV max , and TNM staging were generated for estimation of overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…Univariate analysis of 19 studies (3178 patients) explored the prognostic role of SUV max for OS and demonstrated a combined HR of 2.54 (95%CI: 1.86–3.49, P <0.00001, I 2 = 86%) ( Fig 4A ). I 2 was not statistically significant (17 studies, 2698 patients, P = 0.19, I 2 = 23%) after the exclusion of two studies [ 34 , 39 ] with an HR of 2.26 (95%CI: 1.94–2.64). Begg’s test revealed no significant publication bias ( z = 1.47, P = 0.141).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Univariate analysis of 19 studies (3178 patients) explored the prognostic role of SUV max for OS and demonstrated a combined HR of 2.54 (95%CI: 1.86–3.49, P <0.00001, I 2 = 86%) ( Fig 4A ). I 2 was not statistically significant (17 studies, 2698 patients, P = 0.19, I 2 = 23%) after the exclusion of two studies [ 34 , 39 ] with an HR of 2.26 (95%CI: 1.94–2.64). Begg’s test revealed no significant publication bias ( z = 1.47, P = 0.141).…”
Section: Resultsmentioning
confidence: 94%
“…Sensitively analysis was further conducted with significant heterogeneity ( I 2 = 72%, P <0.00001, HR 2.43, 95%CI: 1.76–3.36) for multivariate analysis of SUV max and DFS (2279 patients) ( Fig 2B ) to estimate the effect of each study on the pooled HR by omitting one study at a time. Three studies [ 34 , 44 , 55 ] were omitted, and an HR of 3.24 (2.43–4.33) using a fixed-model was obtained with a decreased I 2 of 38% and a P value of 0.07 in the Q test. The Begg’s test was statistically significant ( z = 2.23, P = 0.026).…”
Section: Resultsmentioning
confidence: 99%
“…Because cancers typically demonstrate greater than physiologic metabolic activity with high glucose uptake, higher FDG uptake on a PET/CT image may be indicative of a more aggressive phenotype. In a variety of malignancies, a higher SUVmax at diagnosis has been associated with inferior survival 8‐18. In breast cancer, there are significant challenges to the use of PET/CT imaging as a prognostic tool, including extensive tumor heterogeneity, variable uptake of FDG, and differential response to subsequent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data analyzed in this study were of patients who underwent PET/CT for internal organ cancer, not for the spine or nervous system, to rule out metastasis. For these patients, PET/CT is essential 1 , 3 , 9 , 11 , 12) .…”
Section: Discussionmentioning
confidence: 99%